Exploring Ergonomic Risks Behind Waste: A Qualitative Study of BankSampah Workers in Samarinda City - Nadinda Maretta Diah Paramita; Iwan M Ramdan; Muhammad Sultan; Ida Ayu Indira Dwika Lestari (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Musculoskeletal disorders are one of the most common occupational diseases occurring in workplaces such as waste banks. Repetitive manual activities performed by workers pose ergonomic risks if not supported by adequate understanding and workplace facilities. Objective : This study aims to analyze ergonomic practices among waste bank workers, explore their perceptions of MSDs risks, and identify the needs for ergonomics-based health promotion that suits the conditions of the waste bank. Research Methods/ Implementation Methods : This study used a qualitative case study design. Data were obtained through interviews with five Bank Sampah Nusantara workers and work observations. Thematic analysis with manual coding was applied, starting from data reduction, assigning codes (labeling relevant data), and grouping codes into themes, and results were presented descriptively. Data validity was ensured through the Member Check technique. Results : The findings showed that workers at Bank Sampah Nusantara did not use assistive tools and only used basic personal protective equipment (PPE). Several workers complained of body pain and fatigue (especially in the hands and feet). Risk perception was generally low. No training related to ergonomics or safe work practices had been conducted in the waste bank. Conclusion/Lesson Learned : Workers expressed the need for training, improved work facilities, and collaboration with external institutions to support occupational health and safety. This highlights the importance of ergonomics-based health promotion interventions in the informal sector to prevent MSDs and raise workers’ awareness of occupational risks.